Barriers and Challenges of Death Penalty Implementation against Corruption Crimes Perpetrators in Indonesia - Zulfan; Husni; Muhammad Hatta; Ramalinggam Rajamanickam (Cendekia : Jurnal Hukum, Sosial dan Humaniora, 2024)
Since the enactment of the anti-corruption law, no perpetrators of corruption in Indonesia have been sentenced to death. The obstacle to implementing the death penalty for corruptors lies in the provisions set forth in Article 2 paragraph (2) of Law No. 31 of 1999 and its Jo. Law No. 20 of 2001 regarding the corruption eradication, which specifies that the death penalty can only be imposed under certain circumstances. The interpretation of "certain circumstances" such as corruption of funds for mitigation against states of danger, natural disasters, social unrest, mitigation of monetary crises, and mitigation of corruption crimes; is determined by other institutions/agencies, which opens up a broader interpretation and debate and is difficult to measure because it is not limitative. To address the issue of corruption crimes, the government must amend the conditions for imposing the death penalty by restricting the interpretation of "certain circumstances" that highlight the severity of state losses due to criminal crimes.